BENTUK-BENTUK TINDAKAN BELANDA TERHADAP PEJUANG PADA MASA REVOLUSI FISIK DI BALI - Ida Bagus Astika Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2018)
[Title: The Forms of Dutch Action on Pejuang at the Physical Revolution in Bali] This article aims to reveal events about the forms of Dutch action against the soldiers during the period of the physical revolution in Bali. This research is qualitative research. The collection is done by documentation and interview techniques. The data collected is processed and organized for interpretation of the data. Based on research conducted it can be concluded that the physical revolution that occurred in Bali from 1945 - 1950 long enough to be maintained by the soldiers againt the Netherlands. This is because the soldier with the people at that time united. Various tactics or strategies were carried out by the soldiers so the Dutch were very difficult to defeat them. In addition to using military force, the Butch also uses other actions to influence people such as: distributing snacks, cigarettes, coins, batik cloth, and rice. The actions taken by the Dutch to the people either directly or indirectly through his spies. The purpose of doing this is for the people to sympathize with the Dutch.